Thermal-oxidation coupled analysis method for unidirectional fiber-reinforced C/SiC composites in air oxidizing environments below 1000 °C. (April 2023) - Zhao, Chenwei; Tu, Zecan; Mao, Junkui
Abstract: The thermal analysis method for unidirectional fiber-reinforced C/SiC composites (C/SiC-UFRC) in air oxidizing environment below 1000 °C is developed, including a mathematical theoretical model and a finite element model. The mathematical model (MM) is established by combining the thermal resistance network method and the oxidation kinetics theory. The influence of oxidation characteristics on C/SiC-UFRC axial thermal conductivity is firstly introduced into MM, which provides a reference for the theoretical calculation method of C/SiC-UFRC axial thermal conductivity under oxidation conditions. The finite element model (FEM) is constructed on the representative volume element (RVE) of C/SiC-UFRC and the numerical heat transfer method. The FEM numerically simulated the microstructure in the oxidation process and firstly be applied to study the effects of oxidation on the micro temperature field and heat transfer of C/SiC-UFRC. Through the mutual confirmation of MM and FEM, the prediction of thermal conductivity of CMC in air oxidation environment is verified. The effects of oxidation time, oxidation temperature and random distribution of initial cracks are investigated to reveal their influences on the heat transfer behavior of C/SiC-UFRC.